SANITARY CONDITION OF OAK STANDS OF THE VELIKOANADOLSKY FOREST AREA - Kobets, O. V. (Forestry and Forest Melioration, 2018)
Introduction During the period of 2007–2013, in Donetsk region, the area of oak forests enveloped in drying processes increased from 1.2 to 17.7 %. The area of oak stands that undergo drying of strong and medium degree is doubled – from 6.4 to 13.1 %. Maturing and mature oak stands and middle-aged oak stands growing in adverse conditions are drying primarily. The aim of research is to analyze the sanitary condition of the oak stands of steppe part of Ukraine and to identify the ways of their condition optimization. Materials and Methods The sanitary condition of the oak stands and the degree of damage are characterized by an index of sanitary condition. The index of the sanitary condition is defined in temporary plots using sanitary rules in forests of Ukraine. Results Pure oak stands have a significantly higher sanitary condition as compared to the mixed oak stands. The index of sanitary condition of oak (Quercus robur L.) in pure and artificial stands of age classes VI–X is increased from 1.65-1.75 to 2.40. The index of the sanitary condition of oak stands of age classes XI–XIII increased from 2.52 to 2.75. Artificial mixed stands are more stable, and the index of the sanitary condition of oak in their composition is lower – 1.50–1.96. The state of coppice stands is worse compared to the artificial ones. Pure coppice oak stands of age classes VI–VII are weakened (the index of the condition is 2.30–2.50). Beginning on age class VIII, pure oak stands are damaged in medium degree and are highly weaken. The sanitary condition of oak in mixed coppice stands is better compared with pure ones, the index of the sanitary condition is increased from 1.70 (age class VI) to 2.70 (age class X). In pure oak stands, the share of trees of 1 and 2 sanitary condition categories decreased from age classes VI to XIII almost by half – from 80 % to 45 %. For the corresponding period, the share of healthy and weaken specimens is decreased only by 10–12 % (from 90 % to 78–80 %) in mixed oak stands. The share of oak dead wood in pure and artificial oak stands is increased from 6 % (age class VI) to 15–16 % (age classes XII-XIII). The share of oak dead wood in mixed and artificial oak stands is increased from 4 % to 9–10 %, respectively. The share of oak dead wood of pure and coppice oak stands is increased from 11 % to 20–22 %. The share of dead wood of the oak of mixed and vegetative oak stands is increased from 5 to 18–19%. In pure oak stands, the dead wood is represented by trees of Kraft class II and often – of I, which significantly increased the stock volume of dead wood. If the share of associate species in the composition of the stand is from 1–5 % to 55–64 %, the general index of the sanitary condition is improved (decreased), when compared with pure stands, in 1–29 %. The standard of steppe forest is the stand of moderate density with a closed canopy of complex form. Such plantations are resistant to adverse environmental factors. The condition and structure of most of oak stands of the Velikoanadolsky forest area do not meet standards for steppe forest. Conclusions When creating and growing forests in extreme conditions of the steppe, the mixed stands with the second layer and presence of 2–3 units of associate species in the composition of the first layer should be formed. To reproduce coppice and greatly weakened pure artificial oak stands it is necessary to introduce regeneration felling combined with forest plantations creation.